LB-14. CovidIQ- a Text Message-Based Symptom Surveillance Tracker that Predicts New Areas of Increased Incidence of Covid-19 Disease. (31st December 2020) - Reza, Mohammed; Magen, Eran; Vora, Naheed; Rogers, Katherine; Moll, Debbie; Warren, Elaine; Suryaprasad, Anil; Armas-Kolostroubis, Laura; Cheung, Alice
Abstract: Background: Testing for SARS-CoV-2 is limited, making it difficult to estimate the true prevalence of disease and control the spread of new cases. Therefore, finding other ways to diagnose new cases of Covid-19 early is essential for preventing further spread of SARS-CoV-2 to other people in the community and prevent further outbreaks from occurring. Methods: CovidIQ is a confidential and secure text messaging platform that works by collecting participants' self-reported symptoms. Upon agreeing to participate, users are asked some basic demographic questions including gender, age range, ethnic background, and zip code. Participants are then queried via text message on a weekly or biweekly basis as to what symptoms they are experiencing: none, temperature >99.6F, cough, shortness of breath, headache, fatigue, loss of appetite, loss of sense of smell or taste, diarrhea, body ache, sore throat, and/or chills. The symptoms are further broken down into major and minor criteria, allowing presumptive cases to be identified with more accuracy. The major criteria include elevated body temperature, cough, and shortness of breath. If a participant has any 2 major criteria, 1 major or 2 minor, or 3 minor criteria, they are considered a presumptive positive case. While CovidIQ cannot be used to diagnose individuals, the combined results from many individuals show real-time changes in rates of infection for entire counties. Not all people who develop Covid-19 will need hospitalization. They may remain out in the community unaware of the risk they pose to others. And, because the official count of confirmed cases is delayed by 2–4 weeks from the time of actual infection, CovidIQ can sound the alarm much earlier when rates of infection begin to spike. Advanced warning can help communities and individuals make informed decisions about how they should conduct themselves. Results: CovidIQ identified the spike in COVID-19 cases in Jacksonville/Duval County, Florida a full two weeks before it was reported by the Florida Department of Health and Johns Hopkins University. Prevalence of Suspected COVID-19 Cases Through the Use of the CovidIQ Platform in Relation to Dates of OfficiallyReported Cases, Duval County, FL Conclusion: CovidIQ is a novel tool developed to augment the public health response to this ongoing crisis by informing the public sector of potential new hot spots before areas experience a surge as compared to the current reporting structure. Disclosures: All Authors : No reported disclosures